Penerapan Sistem Informasi Manajemen pada Usaha Kecil Menengah di Provinsi Lampung - Ita Fionita; Betty Magdalena (Jurnal Bisnis Darmajaya, 2015)
Management information system is an economic device companies as the supporting of busniness wheel. This system is a support that ease companies to receive information flow where the information flows come from both internal and external company can be absorbed and presented in a place that is easy to understand, quick and on target includes the current financial information, human resources (HR), marketing and sales strategies that will be built by the company to the issues that will influence business wheel in the company. The aim of this research is to determine the influence of human resource management, electronic systems, and the distribution system in moderation system information for competitive advantage of UKM in Lampung Province.  The method uses descriptive and associative.  The research result shows that human resource management positively and significantly influences competitive advantage with moderation organization information system, electronic system does not significantly influence the competitive advantage with moderation organization information systems, and distribution system significantly influences the competitive advantage with moderation organizational information systems. Key Words: Human Resources Management, Organization Information System Electronic Systems, Distribution System, Competitive Advantage.